The Impact of Religiosity and Individual Prayer Activities on Advanced Cancer Patients' Health: Is There Any Difference in Function of Whether or Not Receiving Palliative Anti-neoplastic Therapy? - Paiva, Carlos Eduardo (Journal of religion and health, 2014)
Consecutive patients (n = 221) presenting for initial consultation at a palliative care outpatient clinic were prospectively interviewed and then followed until death. Individual prayer activity (IPA) and global religion scores were associated with quality of life, symptoms, inflammatory markers, and survival. Analyses were adjusted for whether patients were still receiving anti-neoplastic therapies (ANTs) or not. Higher religion scores were associated with lower levels of inflammation in advanced cancer patients still undergoing ANTs. Additionally, higher IPA was an independent good prognostic factor in patients on active ANTs. Further studies are necessary to confirm these findings and to investigate possible biological mechanisms involved.